Analisis Hukum Terhadap Tantangan Keamanan Siber: Studi Kasus Penegakan Hukum Siber di Indonesia - Rahman Najwa, Fadhila (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2024)
In the increasingly developing digital era, cyber security has become an important issue that requires serious attention, especially in the context of law and law enforcement. Cyberattacks are becoming increasingly sophisticated and troubling, posing significant challenges to law enforcement and personal data protection. This research reveals that although Indonesia has adopted several regulations related to cyber security, such as the Information and Electronic Transactions Law (UU ITE), there are still shortcomings in terms of implementation and consistency. A series of cyber security incidents that occurred in Indonesia highlight the need for increased law enforcement capacity. This article examines the challenges faced by Indonesia in dealing with cyber security issues, with a special focus on legal aspects and law enforcement. Using a qualitative approach, this research analyzes secondary data from legal sources, government policies, and selected case studies to identify gaps in current regulations and provide recommendations for improving cyber security in Indonesia. The main objective of this research is to evaluate the effectiveness of the existing legal framework in dealing with cybercrime and promote cross-sector cooperation in preventing and responding to cyber attacks. The research results show that although Indonesia has made progress in cyber security regulations, there is still an urgent need for increased cooperation between institutions, development of law enforcement capacity, and implementation of legal strategies that are more adaptive and responsive to the dynamics of cyber threats.